Rectal separation using hydroxypropyl methylcellulose in intracavitary brachytherapy of cervical cancer: an innovative approach - Basu, Swapnendu; Manir, Kazi Sazzad; Basu, Abhishek; Ghosh, Koushik (Journal of Contemporary Brachytherapy, 2016)
Purpose: This study was initiated to prove feasibility of hydrogel application in recto-vaginal space in intracavitary brachytherapy (ICBT) of cervical cancer in order to reduce rectal toxicity. Material and methods: In a case of stage IIB cervical cancer, after external beam radiotherapy (EBRT), we planned ICBT 7 Gy x 3 fractions. In 1st fraction (Plan 1), due to narrow separation between rectum and cervix (0.18 cm), only 5 Gy was delivered at point A (with high-risk clinical target volume [HR-CTV] D 90 5.94 Gy, intermediate risk clinical target volume [IR-CTV] D 90 4.54 Gy, rectum D 2cc 5.72 Gy, bladder D 2cc 5.52 Gy, and sigmoid colon 5.82 Gy). In 2nd fraction (Plan 2), interstitial brachytherapy (ISBT) was attempted. For the prescription of 5 Gy, we get dose levels almost similar to the 1st insertion: HR-CTV D 90 (6.7 Gy), IR-CTV D 90 (3.06 Gy), bladder D 2cc (5.7 Gy), rectum D 2cc (4.8 Gy), sigmoid colon D 2cc (1.3 Gy) (separation = 0.23 cm). During 3rd fraction (Plan 3), prior doing interstitial insertion, we instilled 50 cc of hydroxypropyl methylcellulose (Viscomet®) up to the tip of recto-vaginal septum. A repeat computed tomography (CT) scan was done 4 hours after Plan 3 treatment and it was re-planned (Plan 4) to find out migration of hydrogel if any and its dosimetric impact. Results : 9 Gy was delivered to point A with a separation of 1.1 cm in Plan 3 (with HR-CTV D 90 16.4 Gy, IR-CTV D 90 11.3 Gy, rectum D 2cc 3.6 Gy, bladder D 2cc 6.9 Gy, and sigmoid colon 2.2 Gy). We achieved an optimum cumulative EQD 2 dose (HR-CTV D 90 98.4 Gy, IR-CTV D 90 76.1 Gy, rectum D 2cc 67.7 Gy, bladder D 2cc 73.2 Gy, and sigmoid colon 59.3 Gy). Hydrogel volume was decreased in Plan 4 without a major dosimetric changes. Conclusions : Hydrogel instillation is a useful tool for recto-vaginal separation during cervical cancer brachytherapy. It increases therapeutic ratio without any adverse event.